2023
DOI: 10.1002/cphc.202200943
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Early Catalytic Events in the Collagenolysis by Matrix Metalloproteinase‐1

Abstract: The front cover artwork is provided by Dr. Karabencheva‐Christova's group at Michigan Technological University. The images show the initially formed and the catalytically productive conformations of MMP‐1 complex with the Triple Helical Peptide (THP), the free energy profile connecting them as well as the coordination geometry of the catalytic zinc (II). The background shows the collagen macromolecule. Read the full text of the Research Article at 10.1002/cphc.202200649.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results align with earlier studies that demonstrated the role of dynamics for substrate binding, catalysis and as a valuable tool for enzyme engineering together with other computational and experimental approaches. 99,136,137,[197][198][199][200][201][202][203] How the substrate Asp103 hFX binding mode A inuence the catalytic reaction of dioxygen activation? The high spin quintet state of Fe(III)-O-Oc − is reported to be the most favorable spin state for dioxygen activation in non-heme dioxygenases.…”
Section: Resultsmentioning
confidence: 99%
“…The results align with earlier studies that demonstrated the role of dynamics for substrate binding, catalysis and as a valuable tool for enzyme engineering together with other computational and experimental approaches. 99,136,137,[197][198][199][200][201][202][203] How the substrate Asp103 hFX binding mode A inuence the catalytic reaction of dioxygen activation? The high spin quintet state of Fe(III)-O-Oc − is reported to be the most favorable spin state for dioxygen activation in non-heme dioxygenases.…”
Section: Resultsmentioning
confidence: 99%